Loeys-Dietz Syndrome Complicated by Right Coronary Artery Pseudoaneurysm - Yasir Jawaid; Obadah Aqtash; Kanaan Mansoor; Aman N. Ajmeri; Frank Fofie; Ahmed Amro; Larry Dial (Case Reports in Cardiology)
Loeys-Dietz syndrome is a rare autosomal dominant connective tissue disorder notable for rapidly progressive vascular aneurysmal disease and craniofacial defects. Patients are at an increased risk for aneurysm rupture and dissection at younger ages compared to other aneurysmal syndromes. Early surgical intervention is important for prevention of ruptures and/or dissection. The coronary arterial tree is mostly involved as a result of postoperative complications of an aortic root repair. This fact has been sparsely reported. We report a unique case of LDS2 presenting with chest pain that was later diagnosed as a pseudoaneurysm as a result of a right coronary artery graft dehiscence.